Pertumbuhan dan produktivitas beberapa galur tanaman padi (Oryza sativa L.) pada musim tanam gadu - ahmad amri; Sabaruddin Sabaruddin; Marai Rahmawati (Jurnal Ilmiah Mahasiswa Pertanian, 2016)
Abstract. This research aims to know the growth and productivity of some strains of rice plant on dry planting season. This research was carried out in a BBT paddy fields (Integrated Seed Hall) Samahani Kuta Malaka, Aceh Besar Regency of Aceh Province, from Mai to October 2015. This study used a Randomized Design Group- nonfactor with 3 strains of rice that is: 14 1002 E, 11S3 E, 14 1009 and each repeated 3 times, so there are 9 units of the experiment. The observed variables are plant height  and tillers of 2, 3, 4, 5, 6, and 7 weeks after planting, flowering age, age of harvest, panicle length, the weight of 1000 grains of paddy, the percentage of grain contains per clump, the percentage of empty grain per tiller, heavy grain contains per clump, heavy grain contains per plot, and potential yield. There is a difference in growth and high productivity of plants, the length and weight of1000 the panicle. The tallest plants found in strain14E1002, longest panicle found in strains of 11S3 and a weight of 1000 grains found in the highest strain 11S3. Strain 14E1009 in achieving higher per hectare results 7.43 tonnes per hectare at dry planting season. Keywords: growth, productivity, rice,strain,  dry planting season